2017
DOI: 10.1213/ane.0000000000001471
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Echocardiographic Indices of Diastolic Dysfunction and Brain Natriuretic Peptide in Predicting Postoperative Atrial Fibrillation After Noncardiac Surgery

Abstract: In a cohort of patients who had echocardiography and BNP measurements before undergoing major thoracic surgery, this study showed that when evaluated together greater preoperative left atrial diastolic volume index and transmitral flow deceleration time but not BNP levels were independent predictors for POAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
0
15
0
2
Order By: Relevance
“…9,10,12 When we directly compared BNP level to echocardiography-derived parameters to predict POAF in a similar population of patients, indices of left atrial and diastolic dysfunction, but not BNP level, were independently associated with greater risk of POAF. 7 However, in that study, elevations in preoperative BNP level were correlated with older age and increased left atrial size and diastolic dysfunction among patients who mostly had no evidence of clinically significant cardiac dysfunction. 7 Traditionally, elevated atrial natriuretic peptide levels have been demonstrated in patients with heart failure and either ventricular or atrial wall distension.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…9,10,12 When we directly compared BNP level to echocardiography-derived parameters to predict POAF in a similar population of patients, indices of left atrial and diastolic dysfunction, but not BNP level, were independently associated with greater risk of POAF. 7 However, in that study, elevations in preoperative BNP level were correlated with older age and increased left atrial size and diastolic dysfunction among patients who mostly had no evidence of clinically significant cardiac dysfunction. 7 Traditionally, elevated atrial natriuretic peptide levels have been demonstrated in patients with heart failure and either ventricular or atrial wall distension.…”
Section: Discussionmentioning
confidence: 69%
“…7 However, in that study, elevations in preoperative BNP level were correlated with older age and increased left atrial size and diastolic dysfunction among patients who mostly had no evidence of clinically significant cardiac dysfunction. 7 Traditionally, elevated atrial natriuretic peptide levels have been demonstrated in patients with heart failure and either ventricular or atrial wall distension. BNP level may also increase with chronic conditions, such as aging, atrial fibrosis, and inflammation-factors that are also known to contribute to the occurrence of POAF in patients without clinical evidence of cardiac wall stretch or heart failure.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A recent study performed in patients undergoing non-cardiac thoracic surgery demonstrated that increased LA volume index, reduced LA emptying fraction, and transmitral flow deceleration time were predictive of POAF. 38,39 Several prospective and retrospective studies have reported that a larger preoperative LA is associated with POAF after both cardiac valve surgery and CABG. [40][41][42][43][44][45][46][47] More advanced TTE measurements, such as speckletracking and strain analysis of the LA, have recently been investigated in numerous cardiac surgical populations.…”
Section: Imagingmentioning
confidence: 99%
“…Однако понимание предсто-ящего объема оперативного вмешательства и достаточно Практическая медицина Problems of practical health care предоперационная ЭхоКГ не была связана с улучшением послеоперационных результатов [36]. Предоперационные уровни натрийуретических пептидов сильно коррелируют с прогнозом ХСН, послеоперационной смертностью и ос-ложненностью [37,38]. По сравнению с единичным опреде-лением пептидов, серийное улучшает риск-стратификацию по композитным точкам (смерть, нефатальный ИМ) [39].…”
Section: American College Of Surgeons (Acs) National Surgical Qualityunclassified